UPLC-Q-TOF-MS/MS Analysis of Seco-Sativene Sesquiterpenoids to Detect New and Bioactive Analogues From Plant Pathogen Bipolaris sorokiniana - Wang, Yan-Duo; Yang, Jian; Li, Qi; Li, Yuan-Yuan; Tan, Xiang-Mei; Yao, Si-Yang; Niu, Shu-Bin; Deng, Hui; Guo, Lan-Ping; Ding, Gang (Frontiers in Microbiology, 2022)
Seco-sativene sesquiterpenoids are an important member of phytotoxins and plant growth regulators isolated from a narrow spectrum of fungi. In this report, eight seco-sativene sesquiterpenoids (1–8) were first analyzed using the UPLC-Q-TOF-MS/MS technique in positive mode, from which their mass fragmentation pathways were suggested. McLafferty rearrangement, 1,3-rearrangement, and neutral losses were considered to be the main fragmentation patterns for the [M+1]+ ions of 1–8. According to the structural features (of different substitutes at C-1, C-2, and C-13) in compounds 1–8, five subtypes (A–E) of seco-sativene were suggested, from which subtypes A, B/D, and E possessed the diagnostic daughter ions at m/z 175, 189, and 203, respectively, whereas subtype C had the characteristic daughter ion at m/z 187 in the UPLC-Q-TOF-MS/MS profiles. Based on the fragmentation patterns of 1–8, several known compounds (1–8) and two new analogues (9 and 10) were detected in the extract of plant pathogen fungus Bipolaris sorokiniana based on UPLC-Q-TOF-MS/MS analysis, of which 1, 2, 9, and 10 were then isolated and elucidated by NMR spectra. The UPLC-Q-TOF-MS/MS spectra of these two new compounds (9 and 10) were consistent with the fragmentation mechanisms of 1–8. Compound 1 displayed moderate antioxidant activities with IC50 of 0.90 and 1.97 mM for DPPH and ABTS+ scavenging capacity, respectively. The results demonstrated that seco-sativene sesquiterpenoids with the same subtypes possessed the same diagnostic daughter ions in the UPLC-Q-TOF-MS/MS profiles, which could contribute to structural characterization of seco-sativene sesquiterpenoids. Our results also further supported that UPLC-Q-TOF-MS/MS is a powerful and sensitive tool for dereplication and detection of new analogues from crude extracts of different biological origins.